Mechanism of azo dye degradation by ozonation - Lim Ching Swan (School of Environmental Engineering, University Malaysia Perlis, 2012)
This study evaluates the efficiency of ozonation for dye removal, Chemical Oxygen Demand (COD) and Total Organic Carbon (TOC) reduction and identified operational parameters such as contact time, pH and concentration of different type of azo dyes. The azo dyes used in this experiment are Reactive Green 19, Remazol Brilliant Blue 19, Reactive Black 5, and Reactive Red 120. Most of the color can be degraded completely within 10 to 20 minutes. In addition the COD and TOC removal efficiency was observed, as the chromophore are destroyed into partially mineralize to small fragments. The FTIR analysis indicates the cleavage of the dye structure and appearance of new peak after the ozonation process. For the pH evaluation, it had been observed that alkaline condition is more preferable compare to acid condition due to higher formation of OH radicals.